Emerging technologies for education : second International Symposium, SETE 2017, held in conjunction with ICWL 2017, Cape Town, South Africa, September 20-22, 2017, Revised selected papers /: second International Symposium, SETE 2017, held in conjunction with ICWL 2017, Cape Town, South Africa, September 20-22, 2017, Revised selected papers. (2017) - Unknown
No abstract available